PROSEDUR PENERAPAN DIFFERENTIAL OF OTHER BEHAVIOR TERHADAP PERILAKU MENGGANGGU SISWA DI TK SANTA ANNA SURABAYA - Dyah Amelia Susanti; Bakhrudin All Habsy; Ardini Farzana Yurianto; Zelma Setya Kasih; Amalia Hamida (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Abstract: Kindergarten education is an important foundation in children's development, preparing them to enter higher levels of education. One of the main challenges in the learning process in kindergarten is disruptive behavior. This behavior can hinder the learning process not only for the students concerned but also for their classmates and teachers. One approach that can be used to address disruptive behavior in kindergarten students is the application of Differential Reinforcement of Other Behavior (DRO). For this reason, this service aims to find out the procedure for applying DRO to the disruptive behavior of kindergarten students. The research method used is a qualitative method with data collection methods using Classroom Action Research (PTK) supported by participatory observation. The results of the implementation of this DRO application show that the provision of DRO must be carried out periodically so that student's disruptive behavior can be reduced. In addition, for the application of DRO to run more effectively, it needs to be combined with other procedures such as token economy. Keywords: Differential of Other Behavior, Disruptive Behavior, Kindergarten Students Abstrak: Pendidikan TK menjadi fondasi penting dalam perkembangan anak, mempersiapkan mereka untuk memasuki jenjang pendidikan yang lebih tinggi. Salah satu tantangan utama dalam proses pembelajaran di TK adalah perilaku mengganggu siswa. Perilaku ini dapat menghambat proses pembelajaran tidak hanya bagi siswa yang bersangkutan, tetapi juga bagi teman-teman sekelasnya dan guru. Salah satu pendekatan yang dapat digunakan untuk mengatasi perilaku mengganggu pada siswa TK adalah penerapan Differential Reinforcement of Other Behavior (DRO). Untuk itu, pengabdian ini bertujuan untuk mengetahui prosedur penerapan DRO terhadap perilaku mengganggu siswa TK. Metode penelitian yang digunakan yakni metode kualitatif dengan metode pengumpulan data menggunakan Penelitian Tindakan Kelas (PTK) yang didukung dengan observasi partisipatif. Hasil pelaksanaan penerapan DRO ini menunjukkan bahwa pemberian DRO harus dilakukan secara berkala agar perilaku mengganggu siswa dapat dikurangi. Selain itu, agar penerapan DRO dapat berjalan lebih efektif maka perlu digabungkan dengan prosedur lain seperti token ekonomi. Kata kunci: Differential of Other Behavior, Perilaku Mengganggu, Siswa TK